Customer Loyalty in Islamic Digital Banking: Trust as Mediator of Risk, Security, and Reputation - Harun Alrasyid; Khalikussabir Khalikussabir; Nuur Halimatus Sa’diyah Masrukhin (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2026)
Objective: This research aims to examine the effects of risk management, security, and reputation on customer loyalty in Islamic digital banking, with trust acting as a mediating variable. Method: This research uses a quantitative explanatory approach based on cross-sectional survey data collected from 252 Indonesian users of Islamic digital banking services, selected through purposive sampling of active users and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM), with acknowledged limitations regarding generalisability. Result: The findings show that risk management and security have significant positive effects on customer loyalty, both directly and indirectly through trust. Reputation does not have a direct effect on customer loyalty; however, its influence becomes significant when fully mediated by trust, indicating total mediation. Trust is identified as the most influential factor in strengthening customer loyalty. Implication: This suggests that Islamic digital banks should prioritize strengthening risk management and security systems to enhance customer trust, as institutional protection mechanisms contribute to sustainable customer loyalty only when internalized as trust Originality or Novelty: This study provides a comprehensive mediation framework by integrating risk management, security, and reputation simultaneously in explaining customer loyalty through trust within the context of Islamic digital banking in an emerging market.